Bigfoot and other strange beasts - Shone, Rob (Graphic mysteries, 2006)
Provides background information about Bigfoot and other strange beasts, presents the stories of the Yeti, the Wildman of China, and Bigfoot in graphic novel form, and includes a brief debate on whether such creatures exist.